Avaliação dos riscos de impacto ambiental com agrotóxicos usados na produção convencional e integrada do mamão - Pinheiro, Emannuel Berson (2007)
Fruit crop is an important socioeconomic activity for Brazil and Espírito Santo State, where papaya is prominent. However, the impacts caused by the use of pesticides are currently a constant concern all over the world. Brazil, to continue to export, should adopt methods and techniques aimed at quality, without harming the environment. In Espírito Santo, Integrated Production of Papaya was implemented to optimize the productive process, reduce the amount of pesticides used and obtain quality of the production acceptable internationally. The objective of this work is to adapt a method for calculation of the risk of environmental impact of the active ingredients registered in the Ministério da Agricultura, Pecuária e Abastecimento (MAPA) for the culture of papaya in Brazil, and to compare the risks of environmental impact in the systems of conventional and integrated production of papaya in Espírito Santo. The active ingredients used are those registered in the MAPA. The Environmental Impact Quotient (EIQ) was calculated as to form the database for "AgroImpacto Mamão". The application of the database was tested in commercial orchards of papaya located in Linhares ES, and conducted in systems of conventional and integrated production. The method of calculation was shown to be applicable to the pesticides registered in Brazil and "AgroImpacto Mamão", and of easy use. Comparison of the monitored orchards showed that there was a reduction of 71,14% in EIQ in the integrated production, and this would be of 78,69% if "AgroImpacto Mamão" was used.